Anatomical Variations of the External Genitalia in Posterior Cloaca: Clinical Consequences of Misdiagnosis—A Systematic Review of the Literature and the ARM-Net Consortium Experience - Carvalho, Catarina; Morandi, Anna; Samuk, Inbal; Gine, Carlos; Gorter, Ramon; Martinez-Urrutia, Maria Jose; Vilanova-Sánchez, Alejandra (European Journal of Pediatric Surgery, 2024)
Purpose All types of cloacal malformations may be associated with anatomic variations of the external genitalia, including hypoplasia of the labia minora and enlarged clitoris; these variations could be even higher in posterior cloacas (PCs). If a careful physical examination is not performed, patients may be misdiagnosed with ambiguous genitalia (AG), leading to subsequent unnecessary testing, surgeries, or even wrong gender assignment. The aim was to analyze data of patients with PC within the ARM-Net registry, focusing on the description of the genitalia, gender assignment, and its consequences. Additionally, we investigated the presence of AG diagnosis in utero or at birth in patients with PC in the literature.Methods The ARM-Net registry was scanned for PC cases and data on diagnosis were collected. A systematic literature search was conducted using the PubMed, EMbase, and Web-of-Science databases. Descriptive statistics was used to report data.Results Nine patients with PC were identified in the ARM-Net registry. Five patients (55%) were diagnosed with AG, two (22%) were assigned as males and only two patients were correctly assigned as females and diagnosed with PC with respective variations of external genitalia. All patients diagnosed with AG had extensive blood testing including karyotype and hormonal studies. One of the patients who was diagnosed as a male, had surgery for pelvic cystic mass removal, which ultimately led to unaware salpingo-oophorectomy, hysterectomy, and vaginectomy. In the literature we identified 60 patients, 14 (23%) with AG, 1 with clitorolabial transposition and 1 with undeveloped vulva and vagina; 4 patients had normal anatomy. In 40 (67%) patients the anatomy of genitalia was not mentioned.Conclusion Patients with PC are at high risk of being diagnosed with AG or even assigned the wrong gender at birth. In our series two patients were assigned as males, and consequently one of them underwent a highly mutilating surgery. A thorough physical examination together with a high index of suspicion and laboratory workup are mandatory to identify these variations, avoiding further investigations, unnecessary surgeries, and parental stress.
Keywords: anorectal malformation; cloaca; external genitalia; ambiguous genitalia